New Insights into the Potential Roles of 3-Iodothyronamine (T1AM) and Newly Developed Thyronamine-Like TAAR1 Agonists in Neuroprotection - Bellusci, Lorenza; Laurino, Annunziatina; Sabatini, Martina; Sestito, Simona; Lenzi, Paola; Raimondi, Laura; Rapposelli, Simona; Biagioni, Francesca; Fornai, Francesco; Salvetti, Alessandra; Rossi, Leonardo; Zucchi, Riccardo; et al. (Frontiers in Pharmacology, 2017)
3-iodothyronamine (T1AM) is an endogenous high-affinity ligand of the trace amine-associated receptor 1 (TAAR1), detected in mammals in many organs, including the brain. Recent evidence indicates that pharmacological TAAR1 activation may offer a novel therapeutic option for the treatment of a wide range of neuropsychiatric and metabolic disorders. To assess potential neuroprotection by TAAR1 agonists, in the present work we initially investigated whether T1AM and its corresponding 3-methylbiaryl-methane analog SG-2 can improve learning and memory when systemically administered to mice at submicromolar doses, and whether these effects are modified under conditions of MAO inhibition by clorgyline. Our results revealed that when i.p. injected to mice, both T1AM and SG-2 produced memory-enhancing and hyperalgesic effects, while increasing ERK1/2 phosphorylation and expression of transcription factor c-fos. Notably, both compounds appeared to rely on the action of ubiquitous enzymes MAO to produce the corresponding oxidative metabolites that were then able to activate the histaminergic system. Since autophagy is key for neuronal plasticity, in a second line of experiments we explored whether T1AM and synthetic TAAR1 agonists SG1 and SG2 were able to induce autophagy in human glioblastoma cell lines (U-87MG). After treatment of U-87MG cells with 1μM T1AM, SG-1, SG-2 transmission electron microscopy (TEM) and immunofluorescence (IF) showed a significant time-dependent increase of autophagy vacuoles and microtubule-associated protein 1 light chain 3 (LC3). Consistently, western blot analysis revealed a significant increase of the LC3II/LC3I ratio, with T1AM and SG-1 being the most effective agents. A decreased level of the p62 protein was also observed after treatment with T1AM and SG-1, which confirms the efficacy of these compounds as autophagy inducers in U-87MG cells. In the process to dissect which pathway induces ATG, the effects of these compounds were evaluated on the PI3K-AKT-mTOR pathway. We found that 1μM T1AM, SG-1 and SG-2 decreased pAKT/AKT ratio at 0.5h and 4h after treatment, suggesting that autophagy is induced by inhibiting mTOR phosphorylation by PI3K-AKT-mTOR pathway. In conclusion, our study shows that T1AM and thyronamine-like derivatives SG-1 and SG-2 might represent valuable tools to therapeutically intervene with neurological disorders.